2019
DOI: 10.3139/o999.03022019
|View full text |Cite
|
Sign up to set email alerts
|

Integrative manufacturing of thermoset injection molding components with continuous fiber-reinforcement

Abstract: Integrative manufacturing of thermoset injection molding components with continuous fiber-reinforcement A new process for the manufacturing of thermoset injection molding components with local continuous fiber-reinforcement in one shot has been developed. "Dry" textiles or continuous fibers are inserted into the cavity of an injection mold. Subsequently, the continuous fibers are impregnated and embedded into a short-fiber-reinforced thermoset molding compound by the following injection molding process. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Ref. [12] proved the complete impregnation of conductor-like structures based on carbon rovings due to the injection molding process with highly filled thermosets. It was demonstrated that several process parameters directly influence the impregnation quality.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [12] proved the complete impregnation of conductor-like structures based on carbon rovings due to the injection molding process with highly filled thermosets. It was demonstrated that several process parameters directly influence the impregnation quality.…”
Section: Introductionmentioning
confidence: 99%